Historical Studies of the English Parliament - Izdebski, Hubert; Russocki, Stanisław (Czasopismo Prawno-Historyczne, 1972)
Recenzja: Historical Studies of the English Parliament, ed. by E. B. Fryde and E. Mil ler, Cambridge at the University Press 1970. Vol. I — Origins to 1399, Vol. II — 1399 - 1603.